Planning for Recreational Waterway Access in Rural Coastal Settings - Corina Guevara; Charles Sidman; Robert Swett; Alan Hodges (EDIS)
Increasing demand for waterfront land throughout the United States is a long-term trend with a profound impact on the public's ability to access coasts and waterways for recreation. Overcrowding at beaches, boat ramps, and popular destinations in Florida's densely populated coastal areas leads more Floridians and tourists to consider recreating in rural coastal communities that still offer the solitude and natural settings desired by many. According to a recent report sponsored by the Outdoor Industry Association, the provision of public water access has increased outdoor recreation tourism, which could bring much-needed economic benefits to rural areas. However, many of these communities lack planning resources to measure local support and user needs and to estimate the benefits that investments in public-access infrastructure might bring. This 6-page fact sheet describes an approach those communities can use to characterize user needs and to quantify local economic benefits derived from public-access infrastructure with a focus on boat ramp facilities. Written by Corina Guevara, Charles Sidman, Robert Swett, and Alan Hodges, and published by the Florida Sea Grant College Program, April 2016.